Molecular diversity of the base-promoted reaction of phenacylmalononitriles with dialkyl but-2-ynedioates - Zheng, Hui; Han, Ying; Sun, Jing; Yan, Chao-Guo (Beilstein Journal of Organic Chemistry, 2022)
In the presence of tetrabutylammonium bromide (TBAB), the cycloaddition reaction of phenacylmalononitriles with dialkyl but-2-ynedioates in acetonitrile at room temperature resulted in 3,3-dicyano-5-hydroxy-5-arylcyclopent-1-ene-1,2-dicarboxylates in high yields. More importantly, the DABCO-promoted domino reaction of two molecules of each phenacylmalononitrile and dialkyl but-2-ynedioate in acetonitrile at room temperature afforded unique multifunctionalized carboxamide-bridged dicyclopentenes in moderate to good yields and with high diastereoselectivity.
Keywords: carboxamide; cycloaddition; cyclopentene; electron-deficient alkyne; phenacylmalononitrile